Altered skeletal muscle (mitochondrial) properties in patients with mitochondrial DNA single deletion myopathy. Issue 1 (December 2016) - Gehrig, Saskia; Mihaylova, Violeta; Frese, Sebastian; Mueller, Sandro; Ligon-Auer, Maria; Spengler, Christina; Petersen, Jens; Lundby, Carsten; Jung, Hans
Abstract Background Mitochondrial myopathy severely affects skeletal muscle structure and function resulting in defective oxidative phosphorylation. However, the major pathomechanisms and therewith effective treatment approaches remain elusive. Therefore, the aim of the present study was to investigate disease-related impairments in skeletal muscle properties in patients with mitochondrial myopathy. Accordingly, skeletal muscle biopsies were obtained from six patients with moleculargenetically diagnosed mitochondrial myopathy (one male and five females, 53 ± 9 years) and eight age- and gender-matched healthy controls (two males and six females, 58 ± 14 years) to determine mitochondrial respiratory capacity of complex I-V, mitochondrial volume density and fiber type distribution. Results Mitochondrial volume density (4.0 ± 0.5 vs. 5.1 ± 0.8 %) as well as respiratory capacity of complex I-V were lower (P  < 0.05) in mitochondrial myopathy and associated with a higher (P  < 0.001) proportion of type II fibers (65.2 ± 3.6 vs. 44.3 ± 5.9 %). Additionally, mitochondrial volume density and maximal oxidative phosphorylation capacity correlated positively (P  < 0.05) to peak oxygen uptake. Conclusion Mitochondrial myopathy leads to impaired mitochondrial quantity and quality and a shift towards a more glycolytic skeletal muscle phenotype.